Polymer waste as an alternative fuel source - Levchuk, Kateryna; Chyrkin, Oleksii; Balaka, Maksym (Харків: ФОП Бровін О. В., 2024)
The problem of polymer waste processing has two aspects: environmental and energy. On the one hand, we improve the environment by destroying polymer waste. On the other hand, this waste is a hydrocarbon derivative and can be a raw material for obtaining alternative motor fuel that will be used in the fuel and energy state complex. The basis of the developed technology, like other similar ones, is low-temperature controlled pyrolysis of polymers without air access in the presence of catalysts. Synthetic liquid fuel can be separated to obtain gasoline, high-quality diesel fuel and heavy fuel oil during the completion of the technological unit with separation and rectification devices.
Keywords: polymer materials; polymer waste; alternative fuel source; environment; energy; alternative energy fuel; pyrolysis; synthetic fuel; паливо